Proceedings of the Fifth Workshop on Computational Linguistics And Clinical Psychology: From Keyboard to Clinic 2018
DOI: 10.18653/v1/w18-0608
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in language markers of depression online

Abstract: Depression is a global mental health condition that affects all cultures. Despite this, the way depression is expressed varies by culture. Uptake of machine learning technology for diagnosing mental health conditions means that increasingly more depression classifiers are created from online language data. Yet, culture is rarely considered as a factor affecting online language in this literature. This study explores cultural differences in online language data of users with depression. Written language data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Second, PiaP considered the cultural expression of depression in text analysis in the creation of its English-Tagalog lexicon. This includes the mixed usage of Tagalog and English (Taglish), textolog (shortening of words), emoticons, and emojis, thus allowing for the recognition of “possible cultural variations in the expression of depressive symptoms via electronic data” [63,64] and providing a more nuanced screening. Compared with BinDhim et al [65], although they proved the feasibility of using a mobile app for depression screening by utilizing an app that was an electronic version of the Patient Health Questionnaire (PHQ)-9, they did not use text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PiaP considered the cultural expression of depression in text analysis in the creation of its English-Tagalog lexicon. This includes the mixed usage of Tagalog and English (Taglish), textolog (shortening of words), emoticons, and emojis, thus allowing for the recognition of “possible cultural variations in the expression of depressive symptoms via electronic data” [63,64] and providing a more nuanced screening. Compared with BinDhim et al [65], although they proved the feasibility of using a mobile app for depression screening by utilizing an app that was an electronic version of the Patient Health Questionnaire (PHQ)-9, they did not use text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This last criteria also inherently excludes datasets that lack annotation of mental health status altogether (e.g. data dumps of online mental health support platforms and text-message counseling services) (Loveys et al, 2018;Demasi et al, 2019).…”
Section: Selection Criteriamentioning
confidence: 99%
“…Elazar and Goldberg (2018) demonstrated that demographics are implicitly encoded in text data. Wood-Doughty et al (2017) and Loveys et al (2018) both studied differing language use across cultures. The former used a Twitter data set with inferred demographic labels, while the latter used a carefully-curated proprietary data set from 7 Cups of Tea.…”
Section: Related Workmentioning
confidence: 99%